Involvement of salsolinol in the suckling-induced oxytocin surge in sheep - Górski Konrad (DOMESTIC ANIMAL ENDOCRINOLOGY, 2017)
During lactation, the main surge of oxytocin is induced by a suckling stimulus. Previous studies have shown that salsolinol (1-methyl-6,7-dihydroxy-1,2,3,4-tetrahydroisoquinoline), a dopamine-derived compound, stimulates both the synthesis and the release of oxytocin in lactating sheep. The objective of the present study was to verify the hypothesis that salsolinol is involved in the mechanism that generates the oxytocin surge that occurs during suckling. Thus, a structural analogue of salsolinol, 1-methyl-3,4-dihydroisoquinoline (1MeDIQ), known to antagonize some of its actions, was infused into the third ventricle of the brain of lactating sheep nursing their offspring. Serial 30-min infusion of 1 MeDIQ (4 x 60 mu g/60 mu L) or vehicle were administered at 30-min interval from 10 AM to 2 PM. The experimental period in every ewe consisted of a nonsuckling period (10 AM-12 PM) and a suckling period (12 PM-2 PM). Blood samples were collected every 10 min, to measure plasma oxytocin concentration by RIA. In control sheep, oxytocin surges of high amplitude were observed during the suckling period. The oxytocin surges induced by suckling were significantly (P < 0.01) diminished in sheep receiving 1MeDIQinfusions as compared to those that received control infusions. However, no significant effect of 1MeDIQ was observed on basal oxytocin release, before suckling. Furthermore, oxytocin release, as measured by the area under the hormone response curve (AUC), was significantly decreased by the administration of 1 MeDIQduring the suckling period. This study shows that elimination of the effect of salsolinol within the central nervous system of lactating sheep attenuates the oxytocin surge induced by suckling. Therefore, salsolinol may be an important factor in the oxytocin-stimulating pathway in lactating mammals. (C) 2016 Elsevier Inc. All rights reserved.